ChemInform Abstract: Suzuki Cross‐Coupling of 5‐Bromothieno[2, 3‐b]pyridines for the Convenient Synthesis of 8‐Arylpyrido[3′, 2′:4, 5]thieno[3, 2‐d]pyrimidin‐4‐amines. Issue 23 (16th May 2013) - Loidreau, Yvonnick; Levacher, Vincent; Besson, Thierry
Abstract The simple method may be extended to a series of boronic acids in order to create libraries of potential biologically interesting products for structure—activity studies.